Conduction recovery following catheter ablation in patients with recurrent atrial fibrillation and heart failure. (1st August 2017) - Anselmino, Matteo; Matta, Mario; Bunch, T. Jared; Fiala, Martin; Scaglione, Marco; Nölker, Georg; Qian, Pierre; Neumann, Thomas; Ferraris, Federico; Gaita, Fiorenzo
Abstract: Background: Atrial fibrillation (AF) catheter ablation is increasingly proposed for patients suffering from AF and concomitant heart failure (HF). However, the optimal ablation strategy remains controversial. We performed this study to assess the prevalence of pulmonary vein (PV) or linear lesion reconnection in HF patients undergoing repeated procedures. Methods and results: At seven high-volume centres, 165 patients with HF underwent a repeat procedure after a first AF ablation including PV isolation alone (47 patients, group A) or PV isolation plus left atrial lines (118 patients, group B). Group A patients presented more often paroxysmal AF ( p < 0.001), less enlarged left atrium ( p < 0.001) and less left ventricular systolic dysfunction ( p = 0.031) compared to Group B, that more commonly had atypical atrial flutter ( p < 0.001). Forty-one (87%) patients in Group A and 69 (58%) in Group B presented at least one reconnected PV ( p < 0.001). Sixty-one (52%) patients in Group B presented at least one reconnected atrial line (left isthmus or roof). Patients without any reconnected PV ( n = 54, 33%) more frequently experienced persistent AF ( p < 0.001), had longer AF duration ( p = 0.047) and larger left atrial volume ( p < 0.001). Twenty-five patients (15%) with no PV and/or line reconnection did not significantly differ, concerning baseline characteristics, compared to those with at least one reconnected ablation site. Conclusion: As in the general AF population undergoing catheter ablation, PV reconnection is frequent in patients with HF and symptomatic recurrence. However, one third of patients presented arrhythmic recurrences even in the absence of PV reconnection, highlighting the importance of the underlying atrial substrate.